Three-dimensional visualisation improves understanding of surgical liver anatomy - Beermann, Judith; Tetzlaff, Ralf; Bruckner, Thomas; Schöbinger, Maximilian; Müller, Beat P.; Gutt, Carsten N.; Meinzer, Hans-Peter; Kadmon, Martina; Fischer, Lars (Medical education, 2010)
Medical Education 2010: 44: 936-940 Objectives Three-dimensional (3-D) representation is thought to improve understanding of complex spatial interactions and is being used more frequently in diagnostic and therapeutic procedures. It has been suggested that males benefit more than females from 3-D presentations. There have been few randomised trials to confirm these issues. We carried out a randomised trial, based on the identification of complex surgical liver anatomy, to evaluate whether 3-D presentation has a beneficial impact and if gender differences were evident. Methods A computer-based teaching module (TM) was developed to test whether two-dimensional (2-D) computed tomography (CT) images or 3-D presentations result in better understanding of liver anatomy. Following a PowerPoint lecture, students were randomly selected to participate in computer-based testing which used either 2-D images presented as consecutive transversal slices, or one of two 3-D variations. In one of these the vessel tree of portal and hepatic veins was shown in one colour (3-D) and in the other the two vessel systems were coloured differently (3-Dc). Participants were asked to answer 11 medical questions concerning surgical anatomy and four questions on their subjective assessment of the TM. Results Of the 160 Year 4 and 5 medical students (56.8% female) who participated in this prospective randomised trial, students exposed to 3-D presentation performed significantly better than those exposed to 2-D images (p < 0.001). Comparison of the number of correct answers revealed no significant differences between the 3-D and 3-Dc modalities p > 0.1). Male students gave significantly more correct answers in the 3-D and 3-Dc modalities than female students (p < 0.03). The gender difference observed in both 3-D modalities was not evident in the 2-D group (p = 0.21). Conclusions This study showed that 3-D imaging significantly improved the identification of complex surgical liver anatomy. Male students benefited significantly more than female students from 3-D presentations. Use of colour in 3-D presentation did not improve student performance.